2013
DOI: 10.1016/j.apsusc.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution photoelectron spectroscopy analysis of sulfidation of brass at the rubber/brass interface

Abstract: High resolution photoelectron spectroscopy is utilized to investigate the chemical composition at the rubber/brass interface to elucidate the origin of strong adhesion as well as the degradation between rubber and brass. Special attention has been given to copper sulfides formed at the interface during the vulcanization reaction at 170 • C. At least five sulfur-containing species are identified in the adhesive interlayer including crystalline CuS and amorphous Cu x S (x ≃ 2). These copper sulfide species are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…1(d)). The lattice fringes with spacings of 0.23 and 0.62 nm in the core and shell regions can be attributed to (111) [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…1(d)). The lattice fringes with spacings of 0.23 and 0.62 nm in the core and shell regions can be attributed to (111) [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the PCC wire had large and more numerous voids in the subsurface. The presence of the voids is attributed to the corrosive sulfur that reacts with Cu to form a sulfide, and thus consumes the Cu atoms of the wire [15,16]. To understand the diffusion behavior of each atom, the depth profile of element distribution was obtained by AES, as shown in Figure 1c,d.…”
Section: Methodsmentioning
confidence: 99%
“…To realize strong adhesion between steel and rubber, the compound with the high sulfur concentration (thus, the accelerator/sulfur ratio is lower than the conventional rubber [15]) is usually used. Since the present study was one of a series of our studies that verify steel-rubber adhesion properties [16][17][18], which were found to be largely influenced by the amount of sulfur accumulated at the steel/rubber interface, we examined in the present study kinetic behaviors of sulfur in the steel belt rubber. It is noted that rubber compounds used in other parts of the automotive tires have accelerator/sulfur ratios between 0.5 and 0.7 with 1 phr of an accelerator and 1.5-2 phr of sulfur.…”
Section: Methodsmentioning
confidence: 99%
“…The rubber compound examined in the present study has a very low accelerator/sulfur ratio (0.06), as described in the experimental section. Formulation is typical for the steel belt rubber in which the sulfur additives are used for both crosslink formation in the rubber compound and the formation of cupper sulfides as an adhesive agent between rubber and steel cords embedded in the steel belt [18]. To realize a strong rubber-steel adhesion, a sufficient amount of sulfur is required to be migrated from the rubber compound to the adhesion interface.…”
Section: -mentioning
confidence: 99%